ADB ESLAP Case Study "Dairy value chain in Indonesia" - Vries, Marion de (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented by Marion de Vries, Wageningen Livestock Research at Wageningen University, on 28 June 2021 at the Asian Development Bank (ADB) Webinar on Sustainable Protein Case Study: Outputs and Synthesis of Results.